Growth Regularity and Performance of Steel Reinforcement Passive Film Under Electric Field - Lianfang Sun; Pangang Wu; Wenshan Peng; Hong Fan; Jinze Li; Li Ma; Zihao Wei (Buildings)
Steel reinforcement undergoes passivation in the alkaline environment of concrete, resulting in the spontaneous formation and growth of a protective passive film. Understanding the growth pattern of passive films is crucial for enhancing the corrosion resistance of steel bars. This study investigates the impact of various electric potentials on passive film growth and its dynamic interaction with chloride ions. Furthermore, the behavior of the passive film after removal from the solution under different conditions is also examined. This study visually demonstrates the process of increasing the passivation potential of the passivation film and the degradation and thinning of the over-passivation potential. Chloride ions can significantly reduce the polarization potential and increase the degree of over-passivation degradation. After prolonged detachment from the solution, the integrity of the passivation film decreases. This study comprehensively evaluates the combined effects of external electric fields, the presence of chloride ions, and separation from an alkaline solution on the growth characteristics of the passive film.